The punctuated equilibrium model of public policy: explaining inertia in Singapore’s Mother Tongue policy - Lu, Luke (2022)
This paper suggests an explicatory model for language policy reform (or lack thereof) at the level of the state. This is accomplished by assessing the value of the ‘punctuated equilibrium’ model of public policy analysis (Howlett and Migone, Policy and Society 30(1):53–62, 2011), which I argue can be strengthened by a genealogical approach (Foucault, Social Science Information 10(2):7–30, 1971). Singapore’s Mother Tongue (MT) policy is used as a case for illustration. There is a consensus amongst local linguists (e.g. Tan, World Englishes 33(3):319–339, 2014; Wee, Discourse: Studies in the Cultural Politics of Education 35(5):649–660, 2014) that the current MT policy of assigning an official MT based on one’s race is essentialist and untenable in light of language shift toward English and increasing diversity through immigration. Using the model, the MT policy is argued to be part of a larger system of policies that maintain a particular understanding of racial equality through a unique brand of multiracialism. The pressures of increasing immigration and diversity are insufficient as exogenous shocks that might lead to changes to the MT policy. Instead, partisan interests in maintaining this brand of multiracialism serves to entrench existing ethnolinguistic policy positions, contributing to inertia in language policy reform.